Assessment of various parameters using simple non-invasive tests in patients with cardiovascular diseases with or without cardiac rehabilitation. (September 2016) - Ueda, Takashi; Miura, Shin-ichiro; Fujimi, Kanta; Ishida, Toshihisa; Matsuda, Takuro; Fujita, Masaomi; Ura, Yoshiyuki; Kaino, Kouji; Sakamoto, Maya; Horita, Tomoe; Arimura, Tadaaki; Shiga, Yuhei; et al.
Abstract: Cardiac rehabilitation (CR) improves cardiac function and exercise capacity in patients with cardiovascular disease (CVD). Simpler techniques are needed for use by physicians in the examination room to assess the usefulness of CR. We enrolled 46 consecutive CVD patients in a CR program (CR group) and prospectively followed them for 3 months. We compared them to 18 age-, gender- and body mass index-matched CVD patients without CR (non-CR group). Various parameters were measured at baseline and after 3 months using 3 simple non-invasive tests: severity of atherosclerosis [arterial velocity pulse index and arterial pressure volume index (API)] were determined using PASESA®, an autonomic nerve total activity amount index and a coefficient of variation of the R–R interval (CVRR) were determined using eHEART®, and peripheral resistance index, pressure rate product, stroke volume and cardiac index were determined using nico®]. There were no significant differences in patient characteristics including percentages (%) of ischemic heart disease and heart failure between the non-CR and CR groups. Systolic blood pressure (SBP), diastolic BP, heart rate and API at baseline significantly decreased and CVRR at baseline significantly increased after 3 months in the CR group, but not in the non-CR group. In addition, ΔAPI (Δ = the value after 3 months minus the value at baseline) was positively associated with ΔSBP in the CR group. In conclusion, CR significantly decreased BP and improved atherosclerosis and sympathetic nerve activity. These findings suggest that simple non-invasive tests may be useful for assessing the effects of CR.